An empirical analysis of Malaysian ringgit equilibrium exchange rate and misalignment - Mohd Sidek, Noor Zahirah; Yusoff, Mohammed (World Business Institute, Australia, 2009)
Following the reinstatement to managed floating exchange rate regime in July 2005, the real effective exchange rate (REER) of Malaysian ringgit (RM) has been fluctuating, albeit, slightly, which raises the question whether the current trend is consistent with the economic fundamentals. This paper attempts to ascertain the degree of misalignment of the ringgit by estimating the long run equilibrium real effective exchange rate of the currency. Based on Johansen vector cointegration technique, we have identified productivity, government consumption expenditure, and trade openness as important determinants of the ringgit long run equilibrium value. Results suggest that the ringgit was persistently overvalued prior to the 1997 crisis. After the crisis, the ringgit fluctuates around its long run equilibrium and the misalignments are eliminated over a relatively short period.